2015
DOI: 10.4084/mjhid.2015.003
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Secondary Malignancies in Chronic Myeloid Leukemia During Therapy With Imatinib Mesylate-Single Institution Experience

Abstract: IntroductionImatinib mesylate (IM) remains the treatment of choice for chronic myeloid leukemia (CML) showing a remarkable efficacy and offers a perspective for long disease-free survival. Due to prolonged administration of IM, the questions about the possible impact on the development of secondary malignancies (SM) are raised.ObjectiveTo investigate the incidence and clinical outcome of secondary malignancies during IM therapy for CML.Material and MethodsThe records of 221 CML patients treated with IM between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…The mechanism for CPCA is still unknown. Although the TKI and their intermediates are genotoxic at high concentration in vitro , some data reported that this phenomenon was not caused by TKI treatment because CPCA could be found in Ph‐negative cells prior to TKI treatment …”
Section: Introductionsupporting
confidence: 89%
“…The mechanism for CPCA is still unknown. Although the TKI and their intermediates are genotoxic at high concentration in vitro , some data reported that this phenomenon was not caused by TKI treatment because CPCA could be found in Ph‐negative cells prior to TKI treatment …”
Section: Introductionsupporting
confidence: 89%
“…Similarly, Helbig et al found that a second malignancy developed in 8 patients (one case each of malignancy of endometrium, testis, skin melanoma, breast, bladder, prostate, large bowel and lung) out of 221 CML patients (3.6%) treated with Imatinib with a median interval of 61 months (10-137 months). However, the risks for second malignancy development as well as for related death in CML patients were not statistically increased if compared to age-adjusted population (9). There was no case of Hodgkin lymphoma detected in the above studies.…”
Section: Case Reportmentioning
confidence: 65%
“…In August 2014, the BCR-ABL was found to be 27.38%. Chromosomal analysis revealed 46XY; t(9;10;22)(q34;p11.2;q11.2) (11)/46, XY (9). Mutation analysis showed E255V mutation in 100% of cells.…”
Section: Case Reportmentioning
confidence: 99%
“…Although secondary tumours have been described after imatinib therapy, the analyses of their frequency with respect to the age-adjusted general population yielded conflicting results 3 4 17 18 19 . Differences in cohort size, follow-up time and the interpretation of the term “secondary cancer” may have been responsible for this difference.…”
Section: Discussionmentioning
confidence: 99%